The theory of the numerical-analytic method: Achievements and new trends of development. III - Ronto, M. I.; Samoilenko, A. M.; Trofimchuk, S. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We analyze results concerning the application of the numerical-analytic method suggested by Samoilenko to delay differential equations, differential equations with “maxima,” functional-differential, operator-differential, and integro-differential equations.